Meningkatkan Pemahaman Konteks Sejarah melalui Pembelajaran Berbasis Teknologi di MAN 3 Pekanbaru - Haidir Haidir (Milenial: Journal for Teachers and Learning, 2022)
This study aims to investigate the use of technology-based learning in improving students' understanding of the historical context at MAN 3 Pekanbaru. This research involved class XI students as the main participants and was conducted for one academic semester. A technology-based learning approach is used by utilizing interactive learning software, documentary videos, and online resources that are relevant to historical content. The research method used is classroom action research with four cycles. Each cycle involves introducing historical material through technology, giving technology-based assignments, group discussions and reflections, and evaluating student understanding. The research data were obtained through tests of understanding the historical context, class observations, and interviews with students. The results showed that there was a significant increase in students' understanding of the historical context after implementing technology-based learning. Student demonstrated higher levels of engagement in learning, as well as better abilities to analyze and relate historical facts to social, political, and cultural contexts. They also demonstrate proficiency in using technology resources to obtain additional information and expand their understanding. The discussion of the findings of this study shows that technology-based learning is effective in increasing students' understanding of the historical context. Technology provides easy access to relevant resources and content, and enables students to learn independently and participate actively in the learning process. In addition, the interaction between technology and students results in an interesting and motivating learning experience.